Chronic Heart Failure in Rheumatoid Arthritis Patients (Part I): Prevalence, Etiology and Pathogenesis - D. S. Novikova; I. G. Kirillova; H. V. Udachkina; T. V. Popkova (Рациональная фармакотерапия в кардиологии)
Rheumatoid arthritis (RA) is a disease with a high cardiovascular risk, which is caused, in particular, by an increased incidence of chronic heart  failure (CHF). Analysis of the results of the main studies on the prevalence of CHF, the features of the etiology and pathogenesis of myocardial dysfunction in RA was the purpose of the review. According to the registers, population and epidemiological studies, the risk of CHF and CHF-associated mortality in RA patients is 1.5-2.5 times higher than in the general population. In most of the studies only clinically manifested congestive heart  failure (HF) was considered, so the actual prevalence of CHF may be significantly underestimated. An increase in the risk of CHF was noted immediately after the debut of RA, with the prevalence of HF with preserved systolic function of the left ventricle, which indicates the important role of diastole disturbance in the pathogenesis of myocardial dysfunction. Chronic systemic autoimmune inflammation contributes to the  development of CHF in RA patients, in addition to coronary heart disease, traditional risk factors (TRFs) of cardiovascular diseases (CVD). Inflammation plays a leading role in the development of CHF through various mechanisms including direct damage to the myocardium and coronary arteries (myocarditis, coronary vasculitis, microcirculatory disorders), aggravation of the severity of TRFs of CVD, accelerated progression of ischemic heart  disease, endothelial dysfunction, increased vascular wall stiffness, cardiac and vascular remodeling. Early diagnosis of CHF and timely measures that can slow its progression is needed due to the high risk of CHF and CHF-associated mortality in RA patients, especially in patients with risk factors for CHF.